2020
DOI: 10.1163/22134808-20191460
|View full text |Cite
|
Sign up to set email alerts
|

Shape Recognition With Sounds: Improvement in Sighted Individuals After Audio–Motor Training

Abstract: Recent studies have demonstrated that audition used to complement or substitute visual feedback is effective in conveying spatial information, e.g., sighted individuals can understand the curvature of a shape when solely auditory input is provided. Recently we also demonstrated that, in the absence of vision, auditory feedback of body movements can enhance spatial perception in visually impaired adults and children. In the present study, we assessed whether sighted adults can also improve their spatial abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This question is particularly interesting with relation to tasks in which vision is classically thought to play a central role, for example, spatial perception. On the one hand, it was commonly accepted that the blind and visually impaired have a significant impairment with respect to their sense of space and capability for forming spatial representations ( Gori et al, 2014 ; Cappagli et al, 2017b ; Martolini et al, 2020a ). However, research now indicates that following dedicated training, the blind can become more capable of spatial localization ( Gaunet et al, 1997 ; Cappagli et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This question is particularly interesting with relation to tasks in which vision is classically thought to play a central role, for example, spatial perception. On the one hand, it was commonly accepted that the blind and visually impaired have a significant impairment with respect to their sense of space and capability for forming spatial representations ( Gori et al, 2014 ; Cappagli et al, 2017b ; Martolini et al, 2020a ). However, research now indicates that following dedicated training, the blind can become more capable of spatial localization ( Gaunet et al, 1997 ; Cappagli et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that individuals with low residual vision (peripheral) were less capable of sound localization and performed worse than both their blind and sighted counterparts ( Lessard et al, 1998 ). Another study showed that children with visual impairments are less capable of updating spatial coordinates as compared to the sighted ( Martolini et al, 2020a ). It could be that in the case of the visually impaired, compensatory neuroplasticity takes place to a lesser extent than in the blind, and yet their vision is severely impaired in comparison to the sighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a previous study that used sound level discrimination and auditory detection tasks (Myers et al, 2020 ) showed that sensorimotor integration may improve the accuracy of the perception of self-generated sounds. Along these lines, in the rehabilitation domain, the association between active body movements and auditory stimuli allows participants to build accurate spatial representations after 30 min of training (Martolini et al, 2020 ). A previous study about spatial auditory memory (Setti et al, 2018 ) showed a significant influence of active exploration in memorizing the spatial organization of a virtual semantic acoustic scene.…”
Section: Discussionmentioning
confidence: 99%